2013
DOI: 10.1556/oh.2013.29597
|View full text |Cite
|
Sign up to set email alerts
|

The cortical collecting duct plays a pivotal role in kidney local renin-angiotensin system

Abstract: A renin-angiotenzin rendszer szervezetünk egyik legjelentősebb hormonális rendszere, amelynek juxtaglomerularis apparátusban történő szabályozása és szerepe jól ismert. Jelen összefoglaló a vese embrionális fejlődésével párhuza-mot állítva a gyűjtőcsatorna renintermelését írja le, valamint ennek lokális szerepét és terápiás célpontként szolgáló lehetőségeit igyekszik feltárni. Nemrégiben került leírásra, hogy krónikus angiotenzin-II-kezelés során, két vese-, egy klip modellben, illetve diabetes mellitusban a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…It is in line with some recent findings, which showed that CD is able to regain renin-producing capacity in pathophysiological states, including high-salt diet, diabetic, or hypertensive nephropathy. 13-17,32 Important to note that this segment does not only contain a larger renin-producing cell population compared to the JGA, but it has high capability for further proliferation. 14 In our studies, we observed a 3- to 4-fold increase in renin content already after 3 weeks of CNI treatment, and because we proved the local expression of renin in the CD and could not detect any glomerulopathy, it is highly unlikely that renin is filtered through the glomerulus and then taken up in the CD.…”
Section: Discussionmentioning
confidence: 99%
“…It is in line with some recent findings, which showed that CD is able to regain renin-producing capacity in pathophysiological states, including high-salt diet, diabetic, or hypertensive nephropathy. 13-17,32 Important to note that this segment does not only contain a larger renin-producing cell population compared to the JGA, but it has high capability for further proliferation. 14 In our studies, we observed a 3- to 4-fold increase in renin content already after 3 weeks of CNI treatment, and because we proved the local expression of renin in the CD and could not detect any glomerulopathy, it is highly unlikely that renin is filtered through the glomerulus and then taken up in the CD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its ability to regulate the sodium, fluid homeostasis, and blood pressure, renin can bear proinflammatory, trophic, and profibrotic properties . Beyond the classical site of renin synthesis in the JGA, in certain pathophysiological conditions, principal cells of the CD can regain the capability to produce renin . In CD, the synthesis of renin can be enhanced not only by its upregulation, but also through the proliferation of renin‐producing principal cells .…”
Section: Introductionmentioning
confidence: 99%